2014
DOI: 10.4137/bmi.s13729
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomic Analysis for the Discovery of Biomarkers in Prostate Cancer

Abstract: Genome-wide association studies (GWAS) have achieved great success in identifying single nucleotide polymorphisms (SNPs, herein called genetic variants) and genes associated with risk of developing prostate cancer. However, GWAS do not typically link the genetic variants to the disease state or inform the broader context in which the genetic variants operate. Here, we present a novel integrative genomics approach that combines GWAS information with gene expression data to infer the causal association between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
(111 reference statements)
0
12
0
Order By: Relevance
“…Several studies have been conducted regarding the location of SNPs and the differences in their rates of occurrence by race. Approximately 100 genes with SNPs are implicated in increasing men’s susceptibility to prostate cancer [ 20 , 21 ]. These are especially accurate because SNPs are stable throughout one’s lifetime, so they cannot be affected by extraneous factors such as lifestyle [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been conducted regarding the location of SNPs and the differences in their rates of occurrence by race. Approximately 100 genes with SNPs are implicated in increasing men’s susceptibility to prostate cancer [ 20 , 21 ]. These are especially accurate because SNPs are stable throughout one’s lifetime, so they cannot be affected by extraneous factors such as lifestyle [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…To address this, we have developed a comprehensive catalogue of germline mutations and genes used in this report and continuously updated it [10, 22, 23, 26, 27]. The details regarding methods of data collection, curation, and annotation, including inclusion and exclusion criteria, have been described in our earlier publications [10, 22, 23, 26, 27] and were based on internationally accepted standards and guidelines proposed by the Human Genome Epidemiology Network for a systematic review of genetic associations [2832]. The data in our catalogue were supplemented with information from the GWAS catalogue [913] which is continuously updated to ensure completeness of the germline variation data used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…7,22 Data collection was based on the guidelines proposed by the Human Genome Epidemiology Network for systematic review of genetic associations. 2630 The details pertaining collection of data used in this study have been reported in our previous published reports.…”
Section: Methodsmentioning
confidence: 99%
“… 7 Indeed, several groups including ours have reported integration of GWAS information with gene expression data in prostate cancer. 20 25 However, the association of GWAS discoveries with primary organ–confined and metastatic disease has not been reported. Similarly, discovery of molecular networks and biological pathways enriched for genetic susceptibility variants involved in the 2 disease states has not been reported.…”
Section: Introductionmentioning
confidence: 99%